Modeling and simulation of an enzymatic reactive absorption process in the internal zone of a rotating packed bed apparatus - Blatkiewicz, Michal; Wojtasik-Malinowska, Justyna; Zawadski, Dawid; Piątkowski, Marcin; Malý, Milan; Hájek, Ondřej; Cejpek, Ondřej; Jaskulski, Maciej (ELSEVIER SCIENCE SA, 2023)
A kinetic model of carbon dioxide absorption within an internal of a rotating packed bed (RPB) apparatus was developed using experimental data. Kinetics of the chemical reaction between carbon dioxide and aqueous solution of N-methyldiethanolamine with and without carbonic anhydrase additive were determined in a flat phase contact surface batch stirred reactor and implemented into the model. Overall pressure drop and absorption efficiency within a metal foam internal were modeled and compared with experimental measurements. The model's predictions of CO2 absorption and pressure drop fit mostly within 20% error range. Validated model served as a tool for further absorption process simulations and sensitivity analysis.

A kinetic model of carbon dioxide absorption within an internal of a rotating packed bed (RPB) apparatus was developed using experimental data. Kinetics of the chemical reaction between carbon dioxide and aqueous solution of N-methyldiethanolamine with and without carbonic anhydrase additive were determined in a flat phase contact surface batch stirred reactor and implemented into the model. Overall pressure drop and absorption efficiency within a metal foam internal were modeled and compared with experimental measurements. The model's predictions of CO2 absorption and pressure drop fit mostly within 20% error range. Validated model served as a tool for further absorption process simulations and sensitivity analysis.
Modeling and simulation of an enzymatic reactive absorption process in the internal zone of a rotating packed bed apparatus
Keywords: rotating packed bed; reactive absorption; carbonic anhydrase; kinetic model; methyldiethanolamine; rotating packed bed; reactive absorption; carbonic anhydrase; kinetic model; methyldiethanolamine